2003
DOI: 10.1089/107999003772084860
|View full text |Cite
|
Sign up to set email alerts
|

Novel Growth and Death Related Interferon-Stimulated Genes (ISGs) in Melanoma: Greater Potency of IFN-βCompared with IFN-α2

Abstract: Interferon (IFN)-dependent cellular effects are mediated by transcriptional induction of responsive genes, collectively referred to as IFN-stimulated genes (ISGs). Which ISGs regulate the potent antiviral, antiproliferative, apoptosis-inducing, antiangiogenic, and immunologic effects of IFNs remains largely undetermined. To identify genes that might be useful for predicting or targeting apoptosis induction in response to IFNs, WM9 melanoma cells were assessed. WM9 cells had equivalent antiviral activity in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 59 publications
7
81
1
1
Order By: Relevance
“…IFN has been also described as an inducer of apoptosis. 41 Consequently, we tested whether the appearance of large colonies could be due to 64G12 neutralizing the apoptotic effect of IFN. Cells after contact with 64G12 were analyzed by Annexin-V staining and flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…IFN has been also described as an inducer of apoptosis. 41 Consequently, we tested whether the appearance of large colonies could be due to 64G12 neutralizing the apoptotic effect of IFN. Cells after contact with 64G12 were analyzed by Annexin-V staining and flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Biological effects of IFNs result from transcriptional regulation of a subset of genes, called IFN-stimulated genes (ISGs). Gene microarray studies have identified >300 induced ISGs in fibrosarcoma or in melanoma cells treated with IFNs (Der et al, 1998;Leaman et al, 2003). ISG products implicated as contributing to IFN-induced apoptosis include Apo2L/TRAIL, FasL, XAF1, protein kinase R, death-associated protein kinase, IRF1, RNaseL and 2-5 OA synthetase .…”
Section: Introductionmentioning
confidence: 99%
“…Both TNFR1 and TNFR2 are capable of triggering apoptosis (1), but this process can be modulated by factors such as MAPK8 signaling, polyamines, and silencer of death domain protein (30,31). Similarly, type 1 IFN can cause programmed cell death (2, 32) and up-regulate genes that drive apoptosis (3,33,34), most likely as part of an antiviral response. However, type I IFNs are not, under most circumstances, cytotoxic and can act as survival factors (4).…”
Section: Discussionmentioning
confidence: 99%
“…A delicate balance is maintained between pathways that promote survival or death, and this balance can be affected by a number of cytokines, including members of the IL, IFN, and TNF families (1). The type 1 IFN in particular have the ability to promote (2,3) or prevent (4) cell death depending on the circumstances. Exposure of cells to stress induces compensatory activation of multiple intracellular signaling pathways, among which is the one controlled by p38 MAPK (MAPK14), also known as stress-activated protein kinase (5).…”
mentioning
confidence: 99%